2008
DOI: 10.1002/jcb.21807
|View full text |Cite
|
Sign up to set email alerts
|

Zm401, a short‐open reading‐frame mRNA or noncoding RNA, is essential for tapetum and microspore development and can regulate the floret formation in maize

Abstract: In flowering plants, pollen formation depends on the differentiation and interaction of two cell types in the anther: the reproductive cells, called microsporocytes, and somatic cells that form the tapetum. Previously, we cloned a pollen specific gene, zm401, from a cDNA library generated from the mature pollen of Zea mays. Expression of partial cDNA of zm401 in maize and ectopic expression of zm401 in tobacco suggested it may play a role in anther development. Here we present the expression and functional cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 44 publications
1
59
0
Order By: Relevance
“…Given its chimeric structure, the novel lncRNA BspUPG2 could have attained neofunctionalization in the context of apomeiosis for pollen development through a number of mechanisms (Kaessmann, 2010), similar to the lncRNAs BcMF11 from Brassica campestris (Song et al, , 2013 and Zm401 in maize (Zea mays; Ma et al, 2008). BspUPG2 could conceivably have a regulatory function via a homology-dependent gene-silencing (HDGS) mechanism (for review, see Meyer and Saedler, 1996), such as posttranscriptional gene silencing of related Figure 8.…”
Section: Bspupg2 Is a Long Pri-mirna With Potential Regulatory Functimentioning
confidence: 99%
“…Given its chimeric structure, the novel lncRNA BspUPG2 could have attained neofunctionalization in the context of apomeiosis for pollen development through a number of mechanisms (Kaessmann, 2010), similar to the lncRNAs BcMF11 from Brassica campestris (Song et al, , 2013 and Zm401 in maize (Zea mays; Ma et al, 2008). BspUPG2 could conceivably have a regulatory function via a homology-dependent gene-silencing (HDGS) mechanism (for review, see Meyer and Saedler, 1996), such as posttranscriptional gene silencing of related Figure 8.…”
Section: Bspupg2 Is a Long Pri-mirna With Potential Regulatory Functimentioning
confidence: 99%
“…Other putative lncRNAs such as CsM10 from cucumber (Cho et al 2005 ) and zm401 from maize (Dai et al 2004 ;Ma et al 2008 ) have been found to be expressed in somatic tapetal cells, developing male gametophyte and might function in male reproductive development. Transgenic plants with downregulated zm401 transcripts exhibited abnormal development of the tapetum, leading to the production of infertile pollen grains (Grant-Downton and Rodriguez-Enriquez 2012 ).…”
Section: Regulatory Role Of Lncrnas In Plant Developmentmentioning
confidence: 97%
“…Forward and reverse genetic studies deduced a function for Zm401 in regulating the expression of critical genes necessary for pollen development including ZmMADS2, MZm3-3 and ZmC5. 112,113 MZm3-3 was upregulated in Zm401 mutants while ZmMADS2 and ZmC5 were both downregulated. 113 Overexpression of Zm401 severely affects pollen development due to abnormal tassels and degenerate anthers.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 98%
“…112,113 MZm3-3 was upregulated in Zm401 mutants while ZmMADS2 and ZmC5 were both downregulated. 113 Overexpression of Zm401 severely affects pollen development due to abnormal tassels and degenerate anthers. 112 How this lncRNA can mediate the downregulation of certain genes but the upregulation of others is intriguing and remains to be elucidated.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 98%